Targeting Reactive Oxygen Species in Cancer via Chinese Herbal Medicine. (10th September 2019) - Qian, Qiaohong; Chen, Wanqing; Cao, Yajuan; Cao, Qi; Cui, Yajing; Li, Yan; Wu, Jianchun
Abstract : Recently, reactive oxygen species (ROS), a class of highly bioactive molecules, have been extensively studied in cancers. Cancer cells typically exhibit higher levels of basal ROS than normal cells, primarily due to their increased metabolism, oncogene activation, and mitochondrial dysfunction. This moderate increase in ROS levels facilitates cancer initiation, development, and progression; however, excessive ROS concentrations can lead to various types of cell death. Therefore, therapeutic strategies that either increase intracellular ROS to toxic levels or, conversely, decrease the levels of ROS may be effective in treating cancers via ROS regulation. Chinese herbal medicine (CHM) is a major type of natural medicine and has greatly contributed to human health. CHMs have been increasingly used for adjuvant clinical treatment of tumors. Although their mechanism of action is unclear, CHMs can execute a variety of anticancer effects by regulating intracellular ROS. In this review, we summarize the dual roles of ROS in cancers, present a comprehensive analysis of and update the role of CHM—especially its active compounds and ingredients—in the prevention and treatment of cancers via ROS regulation and emphasize precautions and strategies for the use of CHM in future research and clinical trials.